An Alternative Methodology of Fair‐Weather Identification for Ground‐Based Measurement of AEF at the Polar Region. Issue 5 (6th March 2023) - Minamoto, Yasuhiro; Kamogawa, Masashi; Kadokura, Akira; Sato, Mitsuteru; Omiya, Satoshi
Abstract: We present a novel method to discriminate atmospheric electric field (AEF) variations originating from the global electrical circuit and local meteorological‐induced AEF variations. By comparing the AEF values measured at two different heights, the method identifies the AEF data including disturbances caused by charged blowing snow particles, and provides the fair‐weather AEF data. The intense positive (fair‐weather direction) apparent AEF was measured during strong winds because of the collision of negatively charged blowing snow particles into the sensor electrode of the electric field mill. In general, the volume density of blowing snow particles rapidly decreases with increasing height. Therefore, measured AEF values at the two heights were different. The difference between AEF values measured at the two heights increased at a wind speed of 6 m/s or more. Meanwhile, the statistical analysis showed that the AEF with and without clouds was less than approximately 1 V/m at Syowa Station, which is negligible. In addition, this case study at Syowa Station found no relationship between cloud extension/dissipation and AEF. Accordingly, we propose a practical method to identify the fair‐weather conditions by the AEF values at two heights and wind speed observed in the polar region, such as at Syowa Station. When we employ criteria that the difference between the AEF observed at the 1.4 and 10 m heights was within ±20 V/m under the wind speed with less than 6.0 m/s to the whole data at Syowa Station, 24% of them were identified as fair‐weather data. Plain Language Summary: Under the fair‐weather conditions on the ground, there is an atmospheric electric field (AEF) of about 100 V/m in the positive polarity from the upper atmosphere to the ground. In the polar regions, the AEF measurements have been often conducted, because there are a small number of aerosols which are a source of noise in AEF measurements under the fair‐weather conditions. However, blowing‐snow that frequently occurs in the polar regions are the major source of noise in AEF measurements due to the electrified snow particles. We have shown that the use of two different height AEF observations and wind speed data allows us to identify the noisy period originating from the electrified snow. In general, the AEF measurements, clouds are also a source of electric disturbance for the fair‐weather AEF. However, at Showa Station in Antarctica, the influence of clouds on the AEF measurements was found to be negligible. Thus, we conclude that this method, which can identify the fair‐weather period without various optical observation, would contribute to the study of global electric circuits. Key Points: A novel fair‐weather identification of atmospheric electric field (AEF) in polar region for the study of global electrical circuit is proposed Two different height observations of AEF with the wind speed data identify snow‐origin signal